Simulation to Improve Trainee Skill and Comfort with Forceps-Assisted Vaginal Deliveries - Rose, Kelsey; Jensen, Kirsten; Guo, Rong; Afshar, Yalda (American Journal of Perinatology Reports, 2019)
Objective Simulation training is a powerful learning tool for low frequency events. Forceps-assisted vaginal deliveries (FAVD) are an important tool in reducing cesarean deliveries. The aim of this study is to create a high-fidelity simulation-based curriculum for residency education and investigate pre- and posttest skill and confidence.Methods A prospective cohort study was conducted involving obstetrics and gynecology residents over 2 academic years. Residents participated in one to three FAVD simulation trainings. All sessions involved video, didactic, and hands-on practice. Pre- and postsurvey and skills assessment were conducted to assess confidence, ability to consent, and perform a FAVD. Wilcoxon's signed-rank tests and Kruskal–Wallis tests were used.Results Thirty residents (73%) completed at least one forceps simulation training session. Participants demonstrated significant improvement in confidence (p < 0.005) following training. Before the intervention, there was a disparity in confidence by postgraduate level (p < 0.005); however, this difference was not seen postsimulation (p = 0.24). Residents demonstrated significant improvement in their FAVD skills (p < 0.05), as well as their ability to consent (p < 0.01).Conclusion Simulation training improves residents' perceived confidence in FAVD. Simulation helped to better equalize confidence across classes. FAVD simulations improves resident confidence, skill, and more broadly broadened the armamentarium to decrease the cesarean delivery rate.
Keywords: forceps-assisted vaginal delivery; obstetrics; simulation; medical education; operative delivery